2014
DOI: 10.1038/srep03733
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the heart: Evaluation of conductive nanomaterials for improving implant integration and cardiac function

Abstract: Recently, carbon nanotubes together with other types of conductive materials have been used to enhance the viability and function of cardiomyocytes in vitro. Here we demonstrated a paradigm to construct ECTs for cardiac repair using conductive nanomaterials. Single walled carbon nanotubes (SWNTs) were incorporated into gelatin hydrogel scaffolds to construct three-dimensional ECTs. We found that SWNTs could provide cellular microenvironment in vitro favorable for cardiac contraction and the expression of elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
135
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(139 citation statements)
references
References 56 publications
4
135
0
Order By: Relevance
“…There are several considerations to take into account for fabrication of conductive biomaterials for tissue regeneration of any sort: 204,205 to implantable gelatin/carbon nanotube scaffolds that have helped to increase the functionality of an infarct rat myocardium. 206 Interestingly, an increase in cardiac cell electrical coupling through the gap junction proteins can be seen on the materials without external electrical stimulation. [191][192][193] …”
Section: Conductive Biomaterialsmentioning
confidence: 99%
“…There are several considerations to take into account for fabrication of conductive biomaterials for tissue regeneration of any sort: 204,205 to implantable gelatin/carbon nanotube scaffolds that have helped to increase the functionality of an infarct rat myocardium. 206 Interestingly, an increase in cardiac cell electrical coupling through the gap junction proteins can be seen on the materials without external electrical stimulation. [191][192][193] …”
Section: Conductive Biomaterialsmentioning
confidence: 99%
“…In vivo evidence in mice indicated that therapeutically relevant concentrations of CNTs are non-toxic; thus, there is promise for further in vivo studies with this nanomaterial (Schipper et al, 2008). Lastly, an engineered cardiac tissue consisting of neonatal rat cardiac cells in a gelatin hydrogel with single-walled CNTs (SWNTs) allowed spontaneous contraction and action potentials in vitro in addition to maturation of cardiomyocytes (Zhou et al, 2014). After suturing the graft onto the infarct region in a rat model, with immunosuppression therapy, improved cardiac function 4 weeks post-application and increase in gap junction protein expression was observed (Zhou et al, 2014).…”
Section: (Vlp Vaccine Formentioning
confidence: 99%
“…Metal NPs and carbon nanotubes (CNTs) can increase the conductivity of biomaterial scaffolds (Shin et al, 2013;Shevach et al, 2014;Zhou et al, 2014). ii.…”
Section: (Vlp Vaccine Formentioning
confidence: 99%
See 2 more Smart Citations